American Postfeminist Cinema : Women, Romance and Contemporary Culture - Schreiber, Michele (Traditions in American Cinema EUP., 2014)
In light of their tremendous gains in the political and professional sphere, why is it that most contemporary American films aimed at women still focus almost exclusively on their pursuit of a heterosexual romantic relationship? American Postfeminist Cinema explores this question and is the first book to examine the symbiotic relationship between heterosexual romance and postfeminist culture. The book argues that since 1980, postfeminism's most salient tensions and anxieties have been reflected and negotiated in the American romance film. Case studies from a broad range of Hollywood and indepe.